Effect of Improving Vehicle Fuel Efficiency on Fuel Tax Revenue and Greenhouse Gas Emissions. Issue 1 (January 2015) - Soltani-Sobh, Ali; Heaslip, Kevin; Bosworth, Ryan; Barnes, Ryan
Vehicle fuel economy improvement has proved to be one of the most effective policies in controlling gasoline demand and greenhouse gas emissions in the transportation sector. However, such improvement also results in the decrease of fuel tax revenue, the main funding source for building and maintaining the U.S. transportation infrastructure. Conversely, fuel efficiency improvement reduces the marginal and average cost of travel, thus encouraging drivers to drive more, and that in turn increases gasoline consumption. The objective of this study was to estimate the potential loss of fuel tax revenue and greenhouse gas emissions, dependents of fuel consumption, that resulted from the fuel efficiency improvement. Accordingly, fuel consumption was modeled as a system of equations consisting of vehicle miles traveled and fuel efficiency (in mpg) as two explanatory variables. The model was estimated by the three-stage least squares method, with annual time-series data for Washington State over the period from 1976 to 2011. According to the results, Washington State will have a 106 million loss in revenue and an 8.7% reduction in emissions of carbon dioxide (CO2 ) in 2031.